Oral Epithelial Cells Distinguish between Candida Species with High or Low Pathogenic Potential through MicroRNA Regulation - Márton Horváth (American Society for Microbiology, 2021)

(untitled)
A relatively new topic within the field of immunology involves the role of miRNAs in innate as well as adaptive immune response regulation. In recent years, posttranscriptional regulation of host-pathogenic fungal interactions through miRNAs was also suggested.